Synthesis of porphyrin sensitizers with a thiazole group as an efficient pi-spacer: potential application in dye-sensitized solar cells - Kumar, Rangaraju Satish; Jeong, Hansol; Jeong, Jaemyeng; Chitumalla, Ramesh Kumar; Ko, Min Jae; Kumar, Kempahanumakkagaari Suresh; Jang, Joonkyung; Son, Young-A. (ROYAL SOC CHEMISTRY, 2016)
Herein, we report porphyrin sensitizers for DSSCs, coded CNU-0C8 and CNU-TBU, which were synthesized using a donor-pi-bridge-acceptor approach. The porphyrin sensitizers were subjected to electrochemical experiments to study their electron distribution, intramolecular charge transfer and HOMO-LUMO levels. The optical and photovoltaic properties of these synthesized porphyrins were measured and compared with those of the YD2-OC8 benchmark dye. To further characterize, we simulated the electrochemical and optical properties of the dyes, which are perfectly in agreement with the experimental data. The new CNU-0C8 and CNU-TBU porphyrin sensitizers provided power conversion efficiencies of 6.49% and 3.19%, respectively, compared to a conversion efficiency of 6.10% for YD2-0C8 under similar conditions. These results indicate that CNU-0C8 exhibits better photovoltaic performance than the benchmark YD2-0C8 sensitizer in a liquid 1(-)/I-3(-) redox electrolyte.